To Keep Close: Mothering Amidst Serious Mental Illness and Suffering - Montgomery, Phyllis (My University, 2003)
The desire to mother in women with serious mental illness (SMI) is increasingly recognized by health care professionals. For women with SMI, mothering is often framed as a pathological problem needing a professional response. However, no research could be found concerning the subjective meaning of mothering for women with SMI. This grounded theory study sough to explore how a group of 20 mothers with SMI managed mothering. To Keep Close, a theoretical model, emerged to describe the mothers' efforts to have meaningful relationships with their children in the context of SMI and suffering. To keep close to their children equated to being "normal", "secure" and "responsible" for them. To keep close, they chose strategies that would imitate ideal representations of mother. These strategies included masking, censoring speech and doing motherwork, each intended to make illness invisible. Mothers made choices concerning how they presented self-as-mother and the extent to which the revealed their true identity. However, mothering in illness and suffering became a vortex of contradictions, resulting in their "hitting bottom". They typically sought help from professionals as the last possibility for reconciliation. With such professional guidance, they hoped to return to their values place as mother. In illness and suffering their agency was undermined. These mothers shifted ways of understanding suffering to include their loss of agency in relation to their children. This study's findings demonstrate that the context of mothering is beyond signs and symptoms of mental illness. These mothers emphasized that the biomedical entity did little to represent their mothering realities. To help them reconcile self-as-mother, nurses must acknowledge their difference and the importance of their strategies of invisibility in order to create mothering possibilities sensitive to their situation. It is important to repeat this study with other mothers in difference for theoretical modification.
Keywords: Nursing; Nursing